The next steps in academic integrity - education, awareness, norms, duty and law - Yuehong (Helen); Hanfeng Lin; Xinxin Zhang; Qing Ye (Oxford University Press, 2021)
We conducted and analyzed several internet surveys in order to understand the profile of global research integrity and ethical awareness, encompassing global population distribution. These were (1) the global distribution of Committee of Publishing Ethics (COPE) membership; (2) the global distribution of "Integrity" or "Ethics" journals; (3) the level of academic integrity awareness in European higher education institutions and (4) awareness of academic integrity in the top universities of Asia and Africa. The results of this survey series highlight seriously imbalanced awareness of research integrity and publishing ethics across the world, especially in developing areas with the highest population density. We therefore propose a new index, the "Academic Integrity Awareness Index" for future discussions across the linked spheres of publishing and research.